Systematic Investigation of the Effects of Seven Plant Extracts on the Physiological Parameters, Yield, and Nutritional Quality of Radish (Raphanus sativus var. sativus) - Godlewska, Katarzyna (Front Plant Sci, 2021)
The modern agricultural sector faces the challenge of addressing the needs of the fast-growing global population. This process should be both high-yielding and sustainable, without creating risks for the environment and human health. Therefore, natural products are gaining attention in the production of safe and nutritious food. In a systematic effort to develop affordable and effective biostimulants, we examined the impact of botanical extracts on the growth and physiological parameters of radish plants under field conditions. Ultrasound-assisted extraction, mechanical homogenization, and water were used for the production of potential plant-based biostimulants. Foliar applications of the bio-products, developed and used in our study, have led to an increase in the examined parameters (total yield, dry weight, photosynthetic pigments, vitamin C, nitrates, and micro- and macroelements). A decrease in the total phenolic compounds content was also noted, as well as a varied impact on the steam volatile compounds, fatty acids, sterol, and glucosinolates composition. The most beneficial effects on radish, in terms of physiological and biochemical properties, were found in groups treated with extracts based on the common dandelion, valerian, and giant goldenrod. This innovative approach presented in our study could provide a valuable tool for sustainable horticultural production.